Чувство льда: [роман : в двух книгах] (Александра Маринина) - Маринина Александра Борисовна (2007)
Экземпляры: ф.15 (20161028) / Инвентарный номер: 52614 / Цена: 30.00 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6